Nitrogen concentrations and proportions of ammonium and nitrate in the nutrition and growth of yellow passion fruit seedlings - Barbosa da Silva, Gabriel; de Mello Prado, Renato [UNESP]; Silva, Sylvia Letícia Oliveira; Campos, Cid Naudi Silva; Castellanos, Leónides Gonzáles; Santos, Luiz Cláudio Nascimento dos [UNESP]; Barreto, Rafael Ferreira [UNESP]; Teodoro, Paulo Eduardo (Taylor & Francis, 2020)
Despite the importance of nitrogen (N) supply to plants, there are still doubts concerning the optimal relations of ammonium and nitrate in the nutrition of yellow passion fruit seedlings. This study aims to evaluate the interaction between nitrogen concentrations and ammonium and nitrate proportions in the nutrition, growth, and dry matter production of passion fruit seedlings grown in a substrate with a nutrient solution. The experiment was conducted in a greenhouse in randomized complete block design with three replications in a 4 × 5 factorial design, consisting of four N concentrations (2.5, 5.0, 10.0 and 20.0 mmol L−1) and five ammonium proportions (0, 25, 50, 75 and 100% in relation to the total N supply). At 60 days after transplanting, green color index; accumulation of N, potassium, calcium, and magnesium in roots and shoots; stem diameter; leaf area; root length; nitrogen use efficiency (NUE); and dry matter of roots and shoots were evaluated. For the formation of seedlings of yellow passion fruit, the nutrient solution should have 13 mmol L−1 of N, with 40% of this nutrient in the form of ammonium. The passion fruit is a plant tolerant to ammonium. However, a critical concentration above 5.7 mmol L−1 of NH4+ in the nutrient solution decreases absorption of cations, NUE, and production of dry matter.
Keywords: nitrogen use efficiency; Passiflora edulis; plant nutrition